2015
DOI: 10.1186/s12864-015-1845-1
|View full text |Cite
|
Sign up to set email alerts
|

CspC regulates the expression of the glyoxylate cycle genes at stationary phase in Caulobacter

Abstract: BackgroundThe Cold Shock proteins are RNA binding proteins involved in various cellular processes, including adaptation to low temperature, nutritional stress, cell growth and stationary phase. They may have an impact on gene expression by interfering with RNA stability and acting as transcription antiterminators. Caulobacter crescentus cspC is an essential gene encoding a stationary phase-induced protein of the Cold Shock Protein family and this work had as goal investigating the basis for the requirement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…S5B). Upregulated genes for alkane degradation are ambiguous, the genes maybe induced due to the acetate accumulation in the aceA mutant 27 . Previous studies have revealed that respiration- and proton motive force-related genes were downregulated in P. aeruginosa when glyoxylate is a sole carbon source, because it uses the GS cycle rather than the TCA cycle 10 .…”
Section: Resultsmentioning
confidence: 99%
“…S5B). Upregulated genes for alkane degradation are ambiguous, the genes maybe induced due to the acetate accumulation in the aceA mutant 27 . Previous studies have revealed that respiration- and proton motive force-related genes were downregulated in P. aeruginosa when glyoxylate is a sole carbon source, because it uses the GS cycle rather than the TCA cycle 10 .…”
Section: Resultsmentioning
confidence: 99%
“…2 ), revealing a crucial role of SpdR in these growth phase inductions. The CC0583 and cspD genes were also previously shown to be induced at stationary phase in a DNA microarray assay [ 16 ]. Conversely, the other four downregulated genes either displayed no change in expression in the wild type strain at stationary phase (CC0517, CC0731 and hfq ) or had the corresponding transcript levels decreased (CC1991).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these genes represent candidates to be SpdR-regulated, probably under a distinct condition from the one used in our assays that affects expression and/or activity of this regulatory protein. In fact, both CC0947 and CC2151 were upregulated 3.5-fold at stationary phase in a DNA microarray assay of stationary x exponential phase in PYE [ 16 ], and CC0990 also showed increased expression, but it did not fall within our cutoff criteria.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of significance for comparison among the samples were determined by Student's t test distribution and analysis of variance (ANOVA) ( 18 ). The represented graphical data are expressed as the SD from three independent experiments unless mentioned otherwise.…”
Section: Methodsmentioning
confidence: 99%